In vitro and in vivo drug disposition of cilengitide in animals and human. Issue 2 (17th March 2016) - Dolgos, Hugues; Freisleben, Achim; Wimmer, Elmar; Scheible, Holger; Krätzer, Friedrich; Yamagata, Tetsuo; Gallemann, Dieter; Fluck, Markus
Abstract: Cilengitide is very low permeable (1.0 nm/sec) stable cyclic pentapeptide containing an Arg‐Gly‐Asp motif responsible for selective binding to α v β 3 and α v β 5 integrins administered intravenously (i.v.). In vivo studies in the mouse and Cynomolgus monkeys showed the major component in plasma was unchanged drug (>85%). These results, together with the absence of metabolism in vitro and in animals, indicate minimal metabolism in both species. The excretion of [ 14 C]‐cilengitide showed profound species differences, with a high renal excretion of the parent drug observed in Cynomolgus monkey (50% dose), but not in mouse (7 and 28%: m/f). Consistently fecal (biliary) secretion was high in mouse (87 and 66% dose: m/f) but low in Cynomolgus monkey (36.5%). Human volunteers administrated with [ 14 C]‐cilengitide showed that most of the dose was recovered in urine as unchanged drug (77.5%, referred to Becker et al. 2015), indicating that the Cynomolgus monkey was the closer species to human. In order to better understand the species difference between human and mouse, the hepatobiliary disposition of [ 14 C]‐cilengitide was determined in sandwich‐cultured hepatocytes. Cilengitide exhibited modest biliary efflux (30–40%) in mouse, while in human hepatocytes this was negligible. Furthermore, it was confirmed that the uptake of cilengitide into human hepatocytes was minor and appeared to be passive. In summary, the extent of renal and biliary secretion of cilengitide appears to be highly species specific and is qualitatively well explained using sandwich hepatocyte culture models.